Effective mitigation strategy in early stage of COVID-19 pandemic in China - Xiao-Yue Yu; Chen Xu; Hu-Wen Wang; Rui-Jie Chang; Yin-Qiao Dong; Lhakpa Tsamlag; Shu-Xian Zhang; Yue-Lin Yu; Ru-Si Long; Hui Wang; Yong Cai (BMC, 2020)
Abstract In the past five months, success in control the national epidemic of coronavirus disease 2019 (COVID-19) has been witnessed in China. The implementation of public health measures accounts for the success which include different interventions in the early or later stages of the outbreak. It is clear that although not all measures were universally effective worldwide, their achievements have been significant. More solidarity is needed to deal with this global pandemic with more learning and understanding. Understanding which of the public health interventions implemented in China were effective may provide ideas for international epidemic control.